Optimization of Hydraulic System Performance Under Variable Loads (Strojniški vestnik – Journal of Mechanical Engineering, 2024)
This paper investigates the performance optimization of hydraulic systems under variable loading conditions. Computational analysis was conducted to evaluate pressure variation, energy consumption, and system efficiency. The results show that optimized control strategies improve hydraulic system reliability and operational performance.
Keywords: Hydraulic systems; Variable loads; Performance optimization; Fluid dynamics; Energy consumption